Patient awareness and quality of oral surgery referrals to specialist practice. (21st January 2020) - Jadun, S.; Syed, N.; Drabu, T.; Yates, J.
Abstract: Introduction: Recent years have shown an increase in the number of patients referred from primary care to a secondary care setting for oral surgery treatment. Due to the high volume of referrals to specialist Oral Surgery services, it is paramount that the referrals from dentist to specialists be appropriate and of a high standard. Materials and methods: The first part of this study assessed patients referred to two primary care settings for oral surgery procedures in Manchester, UK, and the second part examined the quality of the referrals undertaken. Results: A total number of 500 referrals were evaluated from January 2016 to June 2016. The average waiting times for the patients was 3–4 weeks. The majority of patients understood why they had been referred and for what treatment. Less than half the patients were aware that they were to be treated under local anaesthetic. A significant number thought they would be treated either under IV sedation or GA. More than half the patients expected the treatment to be performed in a general dental practice although a number thought treatment would be undertaken in a hospital setting. The contact details were correct in 99%. The teeth to be treated were also largely correct for both practices (98%). Importantly, inappropriate radiographs were attached to more than half of the referrals. Conclusion: A patient‐centred approach to specialist referrals would better equip patients to make informed decisions regarding the treatment to be provided. Furthermore, clarification of referrals to Oral Surgery services is required in some cases.